1996
DOI: 10.1021/ma950925c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Shear Alignment in a Lamellar Diblock Copolymer:  Interplay of Frequency, Strain Amplitude, and Temperature

Abstract: Rheo-optical methods are used to examine the combined effect of shear frequency, strain amplitude, and temperature on the direction and kinetics of flow-induced alignment in lamellar block copolymers. The development of shear-induced alignment in a nearly symmetric polystyrene−polyisoprene diblock (ODT ≃ 164 °C) is recorded in real time using flow birefringence as a probe of the transient lamellar orientation distribution. As alignment progresses during large amplitude oscillatory shearing, the birefringence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
183
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(210 citation statements)
references
References 27 publications
25
183
2
Order By: Relevance
“…In some of the systems a third regime is observed at even higher shear rates with a parallel orientation [5,10]. If the starting point is rather a randomly distributed lamellar phase, the first regime is not observed [1,4,12,16]. This last point illustrates that experiments on layered liquids depend on the history of the sample.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…In some of the systems a third regime is observed at even higher shear rates with a parallel orientation [5,10]. If the starting point is rather a randomly distributed lamellar phase, the first regime is not observed [1,4,12,16]. This last point illustrates that experiments on layered liquids depend on the history of the sample.…”
Section: Introductionmentioning
confidence: 85%
“…In this appendix we describe the key ingredients of a suitable Maple program. A good starting point for such an approach are the balance equations for the unknown quantities (16, 18 -20, 27, and 28) along with the energy density (1) in the appropriate approximation. These equations are entered directly in Maple, with the unknown quantities being functions of time and the spatial coordinates.…”
Section: Appendix B: Generating the Set Of Linear Equationsmentioning
confidence: 99%
“…25 The degree of alignment can be controlled by manipulating variables such as the molecular weight, volume ratio of polymer segments, viscoelastic properties of each polymer component, shear rate (or shear frequency for dynamic shearing), force amplitude, and force direction. 21,22,[26][27][28][29] In one example, Albalak, et al, 25 reported a roll-casting technique to align poly(styrene-block-butadiene-blockstyrene) in the through-plane direction using constant shear. Shear and compression alignment techniques were also successfully applied to the BCE poly(styrenesulfonate-block-methylbutelyne) by Park, et al 12 Although the origin of assembly in mechanical alignment is ascribed to the differences in mechanical properties of each domain, the explicit theory behind the mechanism is still debated.…”
Section: Mechanical Alignmentsmentioning
confidence: 99%
“…A third alignment direction, the so called transverse orientation in which the lamellar normal is parallel to the shear direction, has been found to coexist with parallel orientation for entangled poly(styrene-b-ethylenepropylene) (S-EP) diblock copolymer at high frequency and in the strong segregation limit [10]. Other studies have focused on the kinetics of global alignment and have shown that the ordering rate increases with shear frequency, strain amplitude, and temperature [8,11]. Experiments on PS-PI diblocks further show nonlinear effects of the strain amplitude on the alignment rate, and that the time scale for the development of alignment exhibits a power law dependence on the strain amplitude, with an exponent equal to −3 or −5 depending on the stage of alignment and in different frequency regimes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have focused on the kinetics of global alignment and have shown that the ordering rate increases with shear frequency, strain amplitude, and temperature [8,11]. Experiments on PS-PI diblocks further show nonlinear effects of the strain amplitude on the alignment rate, and that the time scale for the development of alignment exhibits a power law dependence on the strain amplitude, with an exponent equal to −3 or −5 depending on the stage of alignment and in different frequency regimes [11]. Furthermore, many experiments have indicated that the motion of topological defects plays an important role in the global alignment of microdomains under shear, including the evolution of kink band defects and tilt boundaries [12], as well as the migration and annihilation of partial focal conic defects, boundaries, and tilt walls [8,13].…”
Section: Introductionmentioning
confidence: 99%